An industrial quality control study on MK Screens, Inc. - Abalos, Maria Lourdes; Dunuan, Lara Mia; Entico, Maria Cecilia; Pe, Jonna (College of Engineering, 2002)
Statistical Quality Control is the application of the statistical tools and concepts in improving the quality system of a product or process. It involves operational techniques and activities that are used to fulfill requirements for quality. MK Screens, Inc. (MKSI) is a progressive, technology-based organization whose strengths are in mechanical engineering, industrial electronics and controls, and software engineering. The project site is MK's Pulilan Plant and is located at Pulilan, Bulacan, with a land area of 5,000 square meters. It currently employs a total of 214 employees and workers. The main ingredient in the company's success is in its use of technology. Unlike other companies content with acquiring equipment to manufacture products, MKSI studies, applies and even refines technologies. As a result, MKSI is able to leverage these into better products and more efficient techniques of manufacturing. Problem identification and cause identification was conducted by the proponents. The four major problems of the company are the deviation in the wire rod diameter achieved at the wire drawing section, the zinc coating thickness variance achieved at the galvanizing section, the high tensile strength achieved at the annealing process, and the presence of cracks and bubbles observed after the galvanizing process. Statistical Process Control, Process Capability Analysis, Quality Cost Analysis, and Acceptance Sampling Analysis were conducted for the completion of the study. These tools were used in order to arrive at sound recommendations. Currently, the company accepts its raw materials with zero inspection. Since raw materials are delivered every month, it is recommended that inspection of raw materials should be done on a monthly basis. For work-in process materials such as HCl, zinc anode and flux, the company can provide manuals on the proper way of handling such materials. Included in the manual are the correct preparation of the HCl, the proper way of checking the composition of the flux, and the right manner to determine the exact amount of zinc anode needed in the process of galvanizing. For each process, workers are advised to constantly monitor the condition of the operation particularly the machine setups like the speed and temperature and work-in process materials. Machine performance should be recorded for future use. For machines, the company is recommended to have bi-monthly calibration and maintenance. This is to keep machine in optimal condition, to ensure incoming raw materials are within specifications and to allow smooth flow of the process. For the improvement of the company's over-all operations, the proponents offer two general recommendations. The group came with two general recommendations, which aim to encourage more participation, cooperation from, and increase enthusiasm of the workers for improved-quality product. The first recommendation is to establish an incentive scheme, wherein the "Worker of the Month" title is awarded to the most diligent worker of the month. This would boost employee morale. The second general recommendation is forming a special team composed of five people, whose members will be composed of one representative from each process department making sure that the whole production department will be involved. The group's task is to monitor the daily operation of their department, identify problems, which may be related to the process or the workers, try to analyze and solve such problems. The main goals of forming this team are to promote team building, to improve quality system, to increase employee flexibility and to increase use of cross-functional teams.